Peningkatan Karakter Bersahabat Melalui Layanan Bimbingan Kelasikal dengan Pendekatan Experiential Learnin - Pranata, Yosep Yoga; Barus, Gendon (Universitas Sanata Dharma, 2019)
This study aims to improve the character of friendliness among the students through class guidance services using the experiential learning approach and measure the effectiveness of class guidance services using the experiential learning approach in students perspective.This research is a Guidance and Counseling action research completed in three cycles. The subjects of this study involved 30 students of class VII B of SMP Aloysius Turi academic year 2016/2017. The instrument of this research was Friendliness Character Test, Self Assesment Scale of Friendly Character, validation scale of the effectiveness of the model in the students perspective. The realibility coefficient of the friendly character test was considered very high (0.885) and self assesment scale for friendship character was categorized as very high (0.950) measured from the Cronbachs alpha. The technique for data analysis used the category for score items, one group pretest-posttest, and paired sample t-test. The result shows that there was a significant development of friendly character before and after the treatment and this model is effective to develop the students friendly character.